A Rare Clinical Case Of Double Scrotum With Ectopic Testicle In a Dog - Bigliardi, Prof Enrico; Bresciani, Carla; Cesaris, Valeria De; Parmigiani, Enrico (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
A two-years old male mixed breed dog weighing 11 kg was brought to the Veterinary Teaching Hospital by its owner because he noticed a pigmented skin zone with a mass lateral to the penis. The patient was in good clinical condition. On clinical examination, only one testicle was found within the scrotum, and a mass lateral to the right site of the penis was present; upon palpation, the mass was presumed to be a testicle. An ultrasound examination confirmed the presence of an ectopic testicle in that position. The dog had normal fertility and testosterone levels were normal. The patient underwent bilateral orchiectomy and was discharged the following day. The peculiarity of this case is the presence of two independent scrota, an ectopic testicle and its adnexa passing through the abdominal wall, was not supposed to be due a migration along the typical male gonad path during descent.